An Inquiry into the Algerian Massacres: By Youcef Bedjaoui, Abbas Aroua, Meziane Ait-Larbi, eds. (Geneva: Hoggar Books, 1999. 1,473 pages.) (American Journal of Islam and Society, 2002)
The book under review offers a monumental, exhaustive and judiciousaccount of"who are the agents behind the 'horrendous violence' that has followedthe consolidation of the military over incumbent authorities?" Theanswer provided by the victors, those with the power to institute their choic esand interpretations, is that the paroxysm of "Islamic fundamentalism" isexacting grisly, gratuitous and ghastly violence on a society they have beenunable to conquer. On the contrary, scholars insist the beneficiaries of theresource rich regions of Algeria, largely unscathed in the carnage, are indicativeof the faceless murderers behind the monstrosity. Moreover, the primaryimportance of these resources to foreign states and corporations indicatescomplicity. Amidst this confusing scenario, An lnqui!J' into the AlgerianMassacres provides a clear analysis of the beastly culprits.Major international human rights organizations and outstanding journalistshave not found the "Islamic fundamentalist" argument compellingand continue to raise the same question: "Who is behind these grisly atrocities?"The evidence unearthed strongly suggests that the unseen hands,responsible for the bloodbath, belong to the Algerian army. In addition,striking corroboration has come from defectors and victims which incriminatesthe Algerian military apparatus and such foreign co-conspirators asthe French government. This allegation is firmly supported by the environsof the savagery, taking place in close proximity to military and policeinstallations, yet raging for long periods with no interference.Further disturbing, this charge against the Algerian authorities becomesincreasingly credible against the backdrop of the hideous record of rape, tortureand mutilation perpetrated by Algerian mjlitary authorities, well documentedby independent human rights monitors and reputable reporters.Noam Chomsky, in his insightful foreword to the book, collaborates this ...